The Investigating CTS connection: Input and output ability in debate for L2 learners: English - Yahya Al Abrar; Nasrullah Nasrullah (Prodi Tadris Bahasa Inggris, 2023)
This qualitative research investigates the critical thinking skill ability on language input ability. However, past researchers failed to identify this and focused on the output and emotional factors, even the background knowledge of the samples is mentioned as a problem. The method used in this research is a Systematic Literature Review. This study investigates the connection between critical thinking and input ability skills within the debate framework. In debate, the spontaneous and responsive ability intrigues the researcher in case of debate. Nevertheless, the forgotten essential in the debate is the input ability, for example, confirming information, summarizing, catching details, listening to the arguments, processing the flaw, and other necessary skills in debate before the output ability. The sources for this literature review are from the past thirty journals before in the past ten years. The data is collected on the internet with the help of Google Scholar and reviewed by summarizing the journals and taking a conclusion with the result revealed. The result of this paper shows that emotional intelligence, output and input ability concern, speaking proficiency and CTS thorough debate framework are related. This means that input ability plays a major key in output production The excitement for the next research is to find a method to equalize the improvement of input abilities rather than focusing on output ability.